Digital Mediatization and Islamic Political Mobilization: A Bibliometric Study of Global Literature - Irman Puansah; Effan Zulfiqar; Soritua Ritonga; Arifana Arifana (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
This study examines the global scholarly landscape on the mediatization of religion and the political mobilization of Islam in the digital era through a bibliometric approach to Scopus-indexed publications from 2015 to 2025. The primary aim of this research is to systematically map publication trends, thematic cluster structures, geographic distribution of authors, as well as the most influential journals and academic actors in the field. Using VOSviewer for data visualization, the analysis reveals a steady increase in publication volume over the past decade, predominantly driven by academic institutions in the Global North, such as the United States, Australia, and Germany. Nevertheless, international collaboration between countries remains limited. Thematic mapping identifies key terms such as Islam, politics, social media, and Islamophobia as interconnected within issues of identity, power, and digital activism. Journals such as The Muslim World and Contemporary Islam emerge as central nodes in the dissemination of knowledge. These findings suggest that while the field continues to grow, there remains a geographic and conceptual imbalance in representation. Therefore, broader participation from scholars in the Global South, integration of interdisciplinary approaches, and the strengthening of inclusive and contextual knowledge production frameworks are essential for a more comprehensive understanding of digital Islam and symbolic politics in the new media era.